Republic of Croatia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues and Statistical Appendix paper analyzes monetary transmission in Croatia. The evidence analyzed in this paper supports the view that monetary policy in Croatia is not an effective tool for aggregate demand management. One of the main conclusions is that financial conditions in the economy are only weakly correlated with the monetary policy stance. Monetary policy can exercise some control over money-market interest rates, but its influence on lending rates is uncertain and comes with long lags. The paper also examines determinants of lending rates and domestic spreads in Croatia.